The Effect of Toll Road Construction on The Daily Income at PT. Jasa Marga (Persero) Tbk - Noor, Sa'ad; Yulianty, Detty; Setiana, Nana (Dinasti International Journal of Digital Business Management, 2025)
The study aims to determine the influence of each toll road construction segment on the daily income. The research employed a quantitative method to get an overview of the daily income at PT. Jasa Marga (PERSERO) Tbk. The results of this study showed: correlation coefficient analysis, determination test, simple regression test, and descriptive statistical analysis. The results revealed that there was a correlation coefficient between "toll road construction" and "daily income" at PT. Jasa Marga (PERSERO) Tbk of r = 0.899, which is classified as very strong, and the determinant coefficient or the magnitude of the influence of "toll road construction" on "daily income" is 80.9%, which is classified as very strong. Based on the results of the study, the researchers concluded that there was a significant influence between toll road construction and daily income at PT. Jasa Marga (PERSERO) Tbk. which is.